Millennial Investment Behavior in the Digital Era: A Multidimensional Analysis - Ulya, Zikriatul; Setiawan, Muarif; Salsabila, Nasywa; Zulhilmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The expansion of digital technology has revolutionized investment patterns, especially among millennials, who are known to be adaptable to innovation. Ease of access to investment also carries risks for those who do not yet understand financial products. The main factors influencing millennial investment behavior include financial literacy, digital education, religiosity, and risk perception. This study aims to analyze the influence of financial literacy, digital education, religiosity, and risk perception on millennial investment behavior in the digital era. The study used a descriptive quantitative approach with an associative explanation method. The study sample consisted of 150 millennial student respondents in Langsa City, Participants were chosen using purposive sampling. The data were collected through questionnaires and analyzed with multiple regression methods. The results showed that financial literacy and digital education had a positive but insignificant effect on investment behavior, suggesting that increased financial knowledge and access to digital education were not sufficient to significantly encourage investment decisions. Conversely, religiosity and risk perception were shown to have a positive and significant effect, meaning that the higher the level of religiosity and the better the understanding of risk, the greater the tendency of millennials to invest. Simultaneously, all four variables significantly influenced investment behavior. Research findings indicate that millennials' investment behavior is influenced not only by financial literacy and digital education, but also by religiosity and risk perception. Therefore, improving literacy, implementing digital education, and strengthening religious values and risk management are crucial for developing wise and sustainable investment behavior.